LIQUIDITY TRAP IN THE UNITED STATES, THE EURO AREA AND JAPAN - Piotr Misztal (Polityki Europejskie, Finanse i Marketing)
When a country falls into a liquidity trap it means that its central bank lacks an effective expansionary monetary policy aimed at increasing consumption and investment demand. Market participants (households and enterprises), instead of increasing demand, accumulate a growing money supply in the form of cash. Keynes argued that for an economy in a liquidity trap, the only way to increase demand in the country and to stimulate the economy is to conduct expansionary fiscal policy by increasing government spending or reducing taxes. The aim of the research is to verify the empirical hypothesis of the liquidity trap in three of the largest economies in the world, formerly known as the Global Triad (i.e. the USA, the euro zone and Japan), after the 2008 financial crisis. Research methods based on literature studies in macroeconomics and finance, as well as statistical methods, were used in the study. All statistical data came from the statistical office of the European Union – EUROSTAT, and from the statistical database of the United Nations Conference on Trade and Development - UNCTADstat.